(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to know the effectiveness of thinking maps in acquiring the concepts of art education among the students of the Institute of Fine Arts in the subject of criticism and artistic analysis. To achieve the goal of the research, the researchers used a one-group experimental design with a pre- and post-test for criticism and technical analysis for its suitability on a sample of fifth-grade students from the Institute of Fine Arts, fifth-grade, and the research sample consisted of (11) students as an experimental group, and to reach the results of the research is a tool The research is represented by a cognitive achievement test for the subject of criticism and technical analysis, the researchers analyzed the data into systematic images for their research using the statistical package for social sciences (spss( The most important results of the search showed the following: 1- The thinking maps strategy had a high ability to attract the attention of the students and increase their participation in the lesson, which led to an increase in the effectiveness of the students towards the lesson, which helped in learning the technical concepts of criticism and business analysis. 2- The ability of the thinking maps strategy to acquire the cognitive information related to the subject of criticism and technical analysis, which is decided in the fifth stage of the Institute of Fine Arts for the female students, which was reflected in their ability to analyze technical issues and their answers to the test items prepared for this purpose. Recommendations: In light of the results and conclusions reached by the researchers, they recommend a number of recommendations, including: 1- The necessity of training learners to use thinking maps because of their great impact on learning technical concepts and visual thinking skills. 2- The necessity for the teacher to participate with his students in preparing and implementing thinking maps. Suggestions: To complement and develop the current research, the researcher suggested the following: Conducting a study similar to the current study to know the effect of the thinking maps strategy on other dependent variables such as expressive performance, self-confidence, and attitude towards the subject, and others.